Clinical trial participation of patients with glioblastoma at The University of Texas MD Anderson Cancer Center. (May 2019) - Harrison, Rebecca A.; Anderson, Mark D.; Cachia, David; Kamiya-Matsuoka, Carlos; Weathers, Shiao-Pei S.; O'Brien, Barbara J.; Penas-Prado, Marta; Yung, W.K. Alfred; Wu, Jimin; Yuan, Ying; de Groot, John F.
Abstract: Background: It is estimated only 8–11% of patients with glioblastoma (GBM) enrol in clinical trials, limiting treatment development. We analysed the clinical and demographic features of patients with GBM enroled in clinical trials at the University of Texas MD Anderson Cancer Center (MDACC). Methods: We reviewed the records of adult patients treated for primary GBM between 2007 and 2012 at the MDACC. A total of 755 patients were identified: 133 were deemed non-eligible, 111 were deemed trial eligible but received standard care and 511 participated in a clinical trial (311 for newly diagnosed glioblastoma [nGBM] and 200 for recurrent glioblastoma [rGBM]). Population characteristics were analysed using descriptive statistics, and survival end-points were evaluated with the Kaplan–Meier method. Results: The median age of clinical trial participants and trial eligible patients was 53.2 years (standard deviation 12.1). Most patients (49.4%) were enroled in a clinical trial protocol for nGBM. The majority of nGBM trial participants were male patients (65.1%), white (86.3%), married (84.4%) and in state (59.9%). Employment status, education, symptoms, tumour location, performance status, extent of resection and treatment facility differed between nGBM trial participants and non-participants. Patients who were eligible but did not enrol tended to be older, have worse performance status and live farther away from the MDACC. Conclusion: Numerous disease and demographic barriers exist in trial enrolment in patients with GBM. This study highlights some of these obstacles, which require attention to improve patient enrolment to clinical trials. Patient and physician engagement in novel therapeutic strategies is essential to improving outcomes in this disease. Highlights: A small minority of patients with glioblastoma enrol in therapeutic clinical trials. Demographic, disease and treatment-related variables influence trial enrolment. Older age and poor functional status are associated with not enroling in trials. Patients living farther from the treating centre were less likely to enrol.